A time elsewhere - Das, J.P. (New Delhi : Penguin Books, 2009)
The quintessential raconteur with an instinctive mastery of form$1 (BThe Hindu In A Time Elsewhere, fiction and history come together in a sweeping narrative spanning fifty years to create a minutely detailed portrait of nineteenth-century Orissa. The novel revolves around the fortunes of the ruling family of Puri. It traces Divyasingh Dev$1 (Bs career as he inherits the throne, becomes a debauch and, ultimately, a murderer who is banished to the Andaman Islands for life. As Divyasingh spirals out of control, his mother Suryamani, the rani of Puri, emerges from behind her veil as the real ruler, shrewdly and gracefully negotiating the pressures brought to bear by the Empire. The book is also an engaging portrayal of the great intellectual and cultural ferment that marked the clash of the east and the west as figures from Oriya history who played crucial roles in culture and politics during that tumultuous time are brought to life. Fakir Mohan Senapati and Radhanath Ray, educationists and writers, lead the charge against the hegemony of the English and Bengali languages. Gourishankar Ray, who helped set up the first Oriya printing press, publishes the Utkal Dipika, a periodical which quickly becomes the conscience keeper for Orissa, and Pyari Mohan Acharya, expelled from school for defying the British authorities, writes Orissa Itihas, a history of Orissa. Lucidly translated from the original Oriya best-seller Desh Kaal Patra, A Time Elsewhere is a riveting account of a half century in the life of a people. It will fascinate both the student of history and the general reader.s
Keywords: Odisha -- History. -- India